Droplet sizing in spray flame synthesis using wide-angle light scattering (WALS) - Aßmann, Simon; Münsterjohann, Bettina; Huber, Franz; Will, Stefan (Applied Physics B-Lasers and Optics, 2020)
In spray flame synthesis the processes of spray formation and evaporation of the single droplets greatly affect the morphology and size of particles formed. An in situ measurement of these parameters is thus essential for process control and development. In this work, wide-angle light scattering (WALS) is applied to measure droplet sizes in a spray flame. The scattering data of the spherical droplets are evaluated by applying Mie-theory. For droplet sizing, the number of characteristic maxima in the scattering pattern and the measured scattering intensities are evaluated. Droplet size distributions and their parameters were determined by repetitive exposures in various heights above the nozzle outlet for two solvents: pure ethanol and a mixture of ethanol and 2-ethylhexanoic acid at a volume ratio of 35/65. While for ethanol the median droplet size decreases with increasing height, it decreases less for the mixture, which in general exhibits increased droplet sizes for all heights compared to pure ethanol. Furthermore, we could show that using air instead of nitrogen as a co-flow barely affects droplet evaporation in the flame.
CRIS-Team Scopus Importer:2020-05-08